(untitled) (Revista do Centro de Estudos Portugueses, 2002)
Este artigo pretende percorrer os sentidos de sertão e sertanejo, tal como foram construídos no âmbito da literatura brasileira, pensando-os como emblemas de visões de nação e nacionalidade e propondo-os como sentidos que convivem e se confrontam na obra de João Guimarães Rosa. Busca ainda, destacando algumas semelhanças entre duas falas (a de Riobaldo, no plano ficcional, e a de Manuelzão, no plano histórico), discutir como a memória desempenha um papel fundamental na construção daqueles sentidos. This article intends to explore the meanings of sertão and sertanejo as they have been constructed within Brazilian Literature, considering them as emblems of visions of nation and nationality and proposing them as meanings which exist and confront one another in the works of João Guimarães Rosa. By pointing out some similarities between two discourses (Riobaldo’s, on the fictional level, and Manuelzão’s, on the historical one), it seeks to discuss how memory plays a central role in the construction of those meanings.